2020
DOI: 10.1177/2515256420946627
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Specialization of OSBP-Related Proteins

Abstract: Lipids are precisely distributed in the eukaryotic cell where they help to define organelle identity and function, in addition to their structural role. Once synthesized, many lipids must be delivered to other compartments by non-vesicular routes, a process that is undertaken by proteins called Lipid Transfer Proteins (LTPs). OSBP and the closely-related ORP and Osh proteins constitute a major, evolutionarily conserved family of LTPs in eukaryotes. Most of these target one or more subcellular regions, and memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 236 publications
(465 reference statements)
0
32
0
Order By: Relevance
“…There are many known LTP classes; of these, OSBP and related ORPs are unique in their ability to transport PI4P and to exchange this phosphoinositide for another lipid [156]. This ability is due to the lipid-binding OSBP-related domain (ORD) in the C-terminal part of the polypeptide, which can accommodate either one PI4P or another lipid molecule (cholesterol or phosphatidylserine) [157].…”
Section: Effects Of Vapb Depletion In Cellular and Animal Models 41 Er-mitochondria Contacts (Figure 1c-box 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…There are many known LTP classes; of these, OSBP and related ORPs are unique in their ability to transport PI4P and to exchange this phosphoinositide for another lipid [156]. This ability is due to the lipid-binding OSBP-related domain (ORD) in the C-terminal part of the polypeptide, which can accommodate either one PI4P or another lipid molecule (cholesterol or phosphatidylserine) [157].…”
Section: Effects Of Vapb Depletion In Cellular and Animal Models 41 Er-mitochondria Contacts (Figure 1c-box 1)mentioning
confidence: 99%
“…The PH domain mediates ORP binding to the membrane on the non-ER side of the contact site, a binding which usually occurs by coincidence detection of PI4P in conjunction with a membrane-associated protein, e.g., the small GTPase Arf1 in the case of the OSBP-Golgi connection. Thus, ORPs use PI4P for membrane recognition by the PH domain and transport this phosphoinositide via the ORD (reviewed in [157]).…”
Section: Effects Of Vapb Depletion In Cellular and Animal Models 41 Er-mitochondria Contacts (Figure 1c-box 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the observation that yeast lacking six of the seven Osh proteins remain viable and lack any strong phenotypes, Osh proteins were initially thought to play redundant roles in the maintenance of cellular lipid homeostasis (Beh et al, 2001). However, Osh proteins can be observed in different cellular locations (Olkkonen and Li, 2013), and crystal structures have shown that, despite their overall similar fold, different ORDs can accommodate different lipid species, phospholipids and/or sterols (Im et al, 2005;de Saint-Jean et al, 2011;Maeda et al, 2013;Tong et al, 2013;Moser Von, Filseck et al, 2015;Delfosse et al, 2020). The apparent redundancy between Osh proteins must therefore rather be due to a redundancy in lipid transport pathways and mechanisms that drive lipid enrichment in different membranes, and/or to compensatory effects between different lipid species.…”
Section: Export Of Ps From the Ermentioning
confidence: 99%
“…Lipid transfer proteins (LTPs) are cytosolic proteins that distribute diverse lipids between organelles, and along with metabolic pathways, regulate the features of cell membranes [1][2][3][4][5][6][7][8][9][10] . Some members of a major family of LTPs, the oxysterol-binding protein-related proteins (ORP)/oxysterol-binding homology (Osh) family, vectorially transfer lipids by exchange mechanisms 11 . In yeast, Osh6p and its closest homologue Osh7p transfer phosphatidylserine (PS), an anionic lipid made in the endoplasmic reticulum (ER), to the plasma membrane(PM) 12 , where this lipid must be abundant to support signaling pathways 13 .…”
Section: Introductionmentioning
confidence: 99%